Mind Mapping as an Innovation in Reading and Writing Learning: A Study of Understanding Arabic Texts - Zulfa Tsalitsatul Muna; Nur Hidayah; Muhajir; Ashley Le Souef; Alyssa Devaney (Alibbaa’: Jurnal Pendidikan Bahasa Arab, 2025)
This research explores the application of the mind mapping method in the qiraâ€™ah and kitabah learning at the Universitas Nahdlatul Ulama Yogyakarta. Employing a qualitative descriptive approach, data were gathered through observations, interviews with lecturer and students, and questionnaires distributed to students. The findings show that the use of mind mapping significantly facilitates students in understanding Arabic texts and enhances their creativity in presenting the main ideas from those texts. Additionally, mind mapping boosts students’ motivation, creating a more engaging and interactive learning experience. Despite some initial challenges in implementation, such as difficulties faced by some students, the method overall succeeded in creating a more enjoyable learning environment. This research suggests additional exploration and development of mind mapping in Arabic teaching to increase its effectiveness.